Effect of Educational Intervention on Awareness, Attitude, and Practices of Mothers Regarding the Prevention of Rheumatic Fever: A Quasi-Experimental Study - Hasan Haghaninejad MD; Nahid Ardian PhD; Seyed Saeed Mazloomy Mahmoudabad PhD; Reyhane Sefidkar PhD; Mojtaba Jokar MD (SAGE Publishing, 2024)
The awareness, attitudes, and practices of mothers regarding rheumatic fever (RF) remain obscure, therefore, this study aimed to assess the level of awareness, attitude, and practice of mothers regarding RF. A Quasi-experimental study was conducted on 100 mothers who visited medical centers in Yazd province in 2023 to evaluate the level of awareness, attitude, and practice, with the results reported after the intervention using self-made questionnaires. Statistical tests such as the Kruskal-Wallis test, T -test, One-Way analysis of variance, and Mann-Whitney were used. A significance level of P  < .05 was assumed. The mean score of awareness was 6.63 (2.6) and 9.52 (2.59), attitude was 12.56 (4.75) and 17.51 (6.72) and practice was 13.97(5.52) and 19.25 (7.04) of mothers regarding rheumatic fever were before and after study, respectively. The results of mixed effects models showed that education has a significant effect on awareness ( P  < .001), attitude ( P  < .001), and practice ( P  < .001). The mean score of attitude, practice, and awareness were increased by 2.98, 5.28, and 4.95, respectively, after the intervention. Based on the findings, it was observed that mothers have a moderate awareness of rheumatic fever (RF) despite the high burden, poor attitude, and practice. The results of the current study also demonstrate the influence of education in promoting positive practices. Effective training can have a positive impact on the awareness, attitudes, and practices of mothers.